11.9k views
5 votes
For a tensile test, it can be demonstrated that necking begins when dσTdεT=σT. Using Equation σT=K(εT)n, determine an expression for the value of true strain at this onset of necking.

User Cam Tullos
by
4.9k points

1 Answer

2 votes

Complete Question

The complete question is shown on the first uploaded image

Answer:

The value of the true strain at the onset of the necking is proved as,
n = \epsilon_T

Step-by-step explanation:

From the question we see that necking begins when


(d \sigma_T)/(d \epsilon_T) = \sigma_T ---(1)

Now we are told that


\sigma_T = K \epsilon ^n _T

So substituting this into equation 1


(d)/(d \epsilon_T) (K \epsilon^n_T) = \sigma_T


K n \epsilon^(n-1)_T = \sigma_T

But we are told in the question that
\sigma_T = K \epsilon ^n _T So,


K n \epsilon^(n-1)_T = K \epsilon ^n _T

Dividing both sides with
K \epsilon ^n _T

We have


(K n \epsilon^(n-1)_T)/( K \epsilon ^n _T) =( K \epsilon ^n _T)/(K \epsilon ^n _T)


n \epsilon_T^(-1) =1


n = \epsilon_T

For a tensile test, it can be demonstrated that necking begins when dσTdεT=σT. Using-example-1
User Ken Wei
by
5.1k points